2019
DOI: 10.1021/acs.jpclett.9b01572
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Optical Properties of Conjugated Molecules by Lewis Acids: Insights from Electronic Structure Modeling

Abstract: Understanding and controlling the optoelectronic properties of organic semiconductors at the molecular level remains a challenge due to the complexity of chemical structures and intermolecular interactions. A common strategy to address this challenge is to utilize both experimental and computational approaches. In this contribution, we show that density functional theory (DFT) calculation is a useful tool to provide insights into the bonding, electron population distribution, and optical transitions of adducts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…2b, Table 1) indicate the emergence of a new, red-shied, optical absorption band upon complexation. 45 As detailed below, the additional optical feature at wavelengths above 600 nm directly reects the section of the polymer backbone interacting with the LA, with regions spatially away from the contact points contributing to the feature that is seen at $520-550 nm, slightly blue-shied from that of the neat oligomer. We observe the largest red-shi of the lowest electronic excitation for BBr 3 (0.30 eV), followed by BCF (0.23 eV) and BF 3 (0.15 eV).…”
Section: Resultsmentioning
confidence: 98%
“…2b, Table 1) indicate the emergence of a new, red-shied, optical absorption band upon complexation. 45 As detailed below, the additional optical feature at wavelengths above 600 nm directly reects the section of the polymer backbone interacting with the LA, with regions spatially away from the contact points contributing to the feature that is seen at $520-550 nm, slightly blue-shied from that of the neat oligomer. We observe the largest red-shi of the lowest electronic excitation for BBr 3 (0.30 eV), followed by BCF (0.23 eV) and BF 3 (0.15 eV).…”
Section: Resultsmentioning
confidence: 98%
“…[17][18][19] The emergence of Lewis acids like tris(pentafluorophenyl)borane, B(C 6 F 5 ) 3 (in short BCF) 20,21 as novel dopant species has opened new routes for efficient p-doping of organic polymers and oligomers. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] The pioneering study by Pingel et al, 27 has identified integer charge transfer between poly(3-hexylthiophen-2,5-diyl) (P3HT) and BCF, but has not been able to fully disclose the underlying physical processes. The recent work by Yurash et al 34 has demonstrated that the doping mechanisms induced by BCF and other Lewis acids is largely mediated by the protonation of a portion of the polymer in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the enhanced electron affinity of N‐based molecules is responsible for the significantly lowered LUMOs, narrowed bandgaps, and lower energy of absorbance. [ 47,48 ] Calculations using ab initio and density functional theory (DFT) methods carried out by Karamanis et al suggested that the intermolecular B←N coordination would trigger extra‐strong one‐ and two‐photon quantum transitions followed by intense transfer of charge, which will then significantly alter the absorption profiles of the molecule systems. [ 49 ]…”
Section: Intermolecular B←n Coordinationmentioning
confidence: 99%